Stakeholders’ Awareness and Acceptability of PRMSU’s Revised Vision Statement and Mission and the Goals and Objectives of the Communication and Information Technology Programs - Mon, Anthony M.; Linga, Elemae R.; Mistica, Sanny Boy M. (Future Science / FSH-PH Publications, 2024)
Vision, mission, goals, and objectives (VMGOs) function as the founda-tion of an educational institution. The Accrediting Agency for Chartered Colleges and Universities in the Philippines (AACCUP) underscored that an educational institution is assessed according to the degree how its VMGOs are achieved, but not in comparison with others. This descrip-tive cross-sectional survey research was used to gauge the level of awareness and acceptability of the stakeholders on the PRMSU vision statement and mission and the goals and objectives (VMGO) of the Communication and Information Technology Programs of PRMSU Sta Cruz Campus. The stakeholders are “very much aware” of the universi-ty’s new vision statement, mission, goals, and objectives of the teacher education program, they have full participation in the revision of the vision statement. The VMGO is clear, understandable, and acceptable as perceived by the stakeholders. Massive information dissemination of the new vision statement in all media types is recommended. Further-more, stakeholders must be encouraged to share their part in realizing the university’s VMGO.